The C-Band All Sky Survey - Copley, C; Charles Copley (2014)
The C-Band All-Sky Survey (C-BASS) is a 1 GHz bandwidth survey of the radio sky in both intensity and polarization at a frequency of 5 GHz and with a resolution of 0.8. Northern and Southern sky coverage is provided by antennas located at the Owen’s Valley Radio Observatory (OVRO) in California, and the MeerKAT support base in South Africa, respectively. The primary science goal of C-BASS is to provide a highly sensitive C-Band all sky intensity and polarization map to augment the WMAP/Planck surveys. Removal of foregound contamination will place a limit on the success of Cosmic Microwave Background (CMB) experiments that attempt to detect the B-Mode polarization of the CMB. We will provide a HEALPix map (Nside=128) with an r.m.s. noise of 0.13 mK/pixel in Stokes Q and Stokes U, and a confusion limited r.m.s. noise of 0.8 mK/pixel in Stokes I. Removal of foregrounds at the higher frequency CMB surveys will be significantly improved by this lower frequency constraint. This thesis describes the development of the C-BASS gain-stabilized receiver capable of making sensitive measurements of both galactic total intensity and polarization. The receiver features a novel digital backend to provide spectral detail across the frequency band of interest. The analog signal conditioning uses a double sideband mixer to mix the RF frequencies to a DC–1000 MHz baseband for digitization. By changing the mixer frequency and/ or duplicating the signal conditioning and digital hardware, the RF frequency coverage can be modified for other projects. I also describe the process of converting a 7.6 m telecommunications dish to a high performance radio astronomy platform. The discussion includes dish surface measurements, optical design, and the development of an inexpensive telescope servo controller. The antenna conversion process and receiver design can be used to significantly reduce capital costs of future experiments, which is especially useful for short timescale experiments. The African VLBI (Nordling, 2012) is currently following a similar route to repurpose antennas across the African continent.